Component reliability assessment of offshore jacket platforms - Kurian, V.J. (Maxwell Science Publications, 2015)
Oil and gas industry is one of the most important industries contributing to the Malaysian economy. To extract hydrocarbons, various types of production platforms have been developed. Fixed jacket platform is the earliest type of production structure, widely installed in Malaysia's shallow and intermediate waters. To date, more than 60 of these jacket platforms have operated exceeding their initial design life, thus making the re-evaluation and reassessment necessary for these platforms to continue to be put in service. In normal engineering practice, system reliability of a structure is evaluated as its safety parameter. This method is however, much complicated and time consuming. Assessing component's reliability can be an alternative approach to provide assurance about a structure's condition in an early stage. Design codes such as the Working Stress Design (WSD) and the Load and Resistance Factor Design (LRFD) are well established for the component-level assessment. In reliability analysis, failure function, which consists of strength and load, is used to define the failure event. If the load acting exceeds the capacity of a structure, the structure will fail. Calculation of stress utilization ratio as given in the design codes is able to predict the reliability of a member and to estimate the extent to which a member is being utilised. The basic idea of this ratio is that if it is more than one, the member has failed and vice versa. Stress utilization ratio is a ratio of applied stress, which is the output reaction of environmental loadings acting on the structural member, to the design strength that comes from the member's geometric and material properties. Adopting this ratio as the failure event, the reliability of each component is found. This study reviews and discusses the reliability for selected members of three Malaysian offshore jacket platforms. First Order Reliability Method (FORM) was used to generate reliability index and the probability of failure of the members. It was found that probability of failure is inversely related to reliability index for component reliability and variation in metocean values does not have much effect on the component reliability. High reliability indices indicate that component level reliability analysis is sufficient. Â© Maxwell Scientific Organization, 2014.